2008
DOI: 10.1111/j.1742-4658.2008.06349.x
|View full text |Cite
|
Sign up to set email alerts
|

Distinct signaling pathways of microtubule inhibitors – vinblastine and Taxol induce JNK‐dependent cell death but through AP‐1‐dependent and AP‐1‐independent mechanisms, respectively

Abstract: Vinblastine and paclitaxel (Taxol) are widely used chemotherapeutic drugs that inhibit the normal function of microtubules causing mitotic arrest and cell death. Despite these similarities, the signaling pathways that mediate and regulate cell death induced by these agents remain incompletely understood. The purpose of this study was to directly compare the two drugs in terms of their ability to activate components of the c‐Jun N‐terminal protein kinase (JNK) pathway, and to establish the importance of these s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
30
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 23 publications
7
30
0
Order By: Relevance
“…JNK also modifies the activity of numerous proteins that reside at the mitochondria or act in the nucleus by phosphorylation of its target proteins (Vlahopoulos and Zoumpourlis, 2004;Waetzig and Herdegen, 2005). JNK activation has been shown in PTX-treated solid tumor cells (Lee et al, 1998;Kolomeichuk et al, 2008). However, the detailed mechanism of JNK in apoptosis procedures remains largely unclear (Shiah et al, 2001;Ohtsuka et al, 2003;Brichese et al, 2004;Wang et al, 2006;Zhang et al, 2006;Small et al, 2007;Selimovic et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…JNK also modifies the activity of numerous proteins that reside at the mitochondria or act in the nucleus by phosphorylation of its target proteins (Vlahopoulos and Zoumpourlis, 2004;Waetzig and Herdegen, 2005). JNK activation has been shown in PTX-treated solid tumor cells (Lee et al, 1998;Kolomeichuk et al, 2008). However, the detailed mechanism of JNK in apoptosis procedures remains largely unclear (Shiah et al, 2001;Ohtsuka et al, 2003;Brichese et al, 2004;Wang et al, 2006;Zhang et al, 2006;Small et al, 2007;Selimovic et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The role of JNKs in cancer is indicated by their ability to cause tumor suppression and induce apoptosis in response to certain anti-cancer drugs (21)(22)(23)(24). However, this increased responsiveness to chemotherapeutics is attenuated in advanced tumors, where JNK signaling is impaired, rendering the cells refractory to chemotherapy (22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…However, this increased responsiveness to chemotherapeutics is attenuated in advanced tumors, where JNK signaling is impaired, rendering the cells refractory to chemotherapy (22)(23)(24). Recently, it has been reported that MEKK1 is one of the 50 genes containing somatic missense and nonsense mutations in various tumors (25), and MEKK1 is required for JNK activation and induction of apoptosis by drugs causing cytoskeletal disruption, indicating the importance of the MEKK1/JNK-dependent apoptotic pathway in carcinogenesis (26).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the molecular mechanisms may be located downstream of TLR domain-containing cytosolic adapters. In fact, microtubule-depolymerizing agents can activate the NF-kB and MAPK signaling pathways efficiently (41,42), although no specific receptors have been identified to date. Further experiments are necessary to address this issue and to define the molecular signaling cascades induced by dolastatins.…”
Section: Discussionmentioning
confidence: 99%